STRATEGI PIMPINAN PESANTREN DALAM PEMASARAN LEMBAGA PENDIDIKAN DI PONDOK PESANTREN BAITUL IHSANI NAHDLATUL WATHAN KECAMATAN TEBO TENGAH KABUPATEN TEBO PROVINSI JAMBI - Yuli Novia Sari; Musli; Ahmad Fikri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the marketing strategy implemented by the Baitul Ihsani Nahdlatul Wathan Tebo Islamic Boarding School to increase the number of new student enrollments amidst increasingly competitive educational institutions. This study used a qualitative approach with descriptive methods to describe the actual conditions of the Islamic boarding school's marketing strategy. Data were collected through observation, interviews, and documentation with the Islamic boarding school leadership, ustadz/ustadzah (Islamic teachers), and students as key informants. The results indicate that the Islamic boarding school's marketing strategy requires systematic planning, continuous evaluation, and strengthening of digital management to compete in the modern era. Furthermore, the success of an educational institution's marketing is greatly influenced by the leadership's managerial capacity, the Islamic boarding school's ability to develop flagship programs, and the strategy's alignment with Islamic values ​​as the institution's spiritual foundation.